Experimental investigation on photothermal conversion properties of collagen solution-based carbon black nanofluid - Xiahua Zuo; Weimin Yang; Zhenghe Zhang; Lijian Song; Hua Yan; Changfeng Guan; Jin Zhan; Wenlei Zhu; Haowei Li; Dailing Zhang; Xin Wen; Ying An (Case Studies in Thermal Engineering, 2022)
Nanofluid shows promising development prospects in solar thermal applications. In this paper, collagen solution-based carbon black (CS-CB) nanofluids in different mass fractions (0.001 wt%, 0.002 wt%, 0.005 wt %, 0.008 wt%, and 0.01 wt%) were prepared using a two-step method. The CS-CB nanofluid morphologies were tested by SEM, TEM, and a laser particle analyzer. The viscosity and heat conductivity of CS-CB nanofluids were analyzed, and the results demonstrated that the flow and heat transfer performance of CS-CB nanofluids was satisfactory. Additionally, the optical properties of CS-CB nanofluids were investigated; carbon black improved the light absorption of the CS-CB nanofluids. The photothermal conversion experiment was conducted both in the laboratory and outdoors. The maximum photothermal efficiency of CS-CB nanofluids was 62.86% throughout the experiment using a solar simulator, which was relatively higher than the maximum photothermal efficiency levels of deionized water and collagen solution, 53.8% and 47.1%, respectively. In the outdoor experiment, the maximum temperature and photothermal conversion efficiency of CS-CB nanofluids were 56.8 °C and 75.1%, respectively. This study confirmed that CS-CB nanofluid was an excellent potential working fluid for direct absorption solar collectors, and more research on this topic is anticipated.